Long-term outcomes of biodegradable polymer biolimus-eluting stents versus durable polymer everolimus-eluting stents: A meta-analysis of randomized controlled trials. (15th November 2016) - Sakurai, Ryota; Burazor, Ivana; Bonneau, Heidi N.; Kaneda, Hideaki
Abstract: Background: Both biodegradable polymer biolimus-eluting stents (BP-BES) and biocompatible durable polymer everolimus-eluting stents (DP-EES) have been developed to decrease the risk of late adverse events. However, their efficacy and safety beyond 1 year after stent deployment still remain controversial. Methods: We conducted a meta-analysis on randomized controlled trials (RCTs) comparing BP-BES with DP-EES in patients undergoing percutaneous coronary intervention in long-term follow up (beyond 1 year), and compared the pooled estimates with those in mid-term follow up (within 1 year). Results: Eight RCTs were included in this meta-analysis. The risks in BP-BES versus DP-EES of death (odds ratio (OR): 1.06, 95% confidence interval (CI): 0.86–1.31, p = 0.557 for long-term; OR: 1.09, 95% CI: 0.76–1.56, p = 0.645 for mid-term), myocardial infarction (OR: 1.06, 95% CI: 0.84–1.35, p = 0.628 for long-term; OR: 1.04, 95% CI: 0.81–1.33, p = 0.778 for mid-term), and definite or probable stent thrombosis (OR: 0.89, 95% CI: 0.51–1.57, p = 0.695 for long-term; OR: 1.36, 95% CI: 0.66–2.81, p = 0.400 for mid-term) were comparable in each follow up, respectively. In contrast, the risk of target vessel revascularization (TVR) tended to be higher in BP-BES as compared to DP-EES in long-term follow up (OR: 1.15, 95% CI: 0.97–1.37, p = 0.098 for long-term; OR: 1.09, 95% CI: 0.87–1.36, p = 0.447 for mid-term). Conclusions: Although the overall clinical outcomes were similar between BP-BES and DP-EES, BP-BES may be associated with higher risk of TVR up to 3 years after stent deployment compared with DP-EES. Further studies are warranted in larger populations of patients during longer-term follow up.